Preparation method of graphene nanometer copper yttrium oxide composite powder
Through the preparation method of graphene nano-copper-yttrium composite powder, the existing photocatalysts have been solved, and the low cost, high efficiency of photocatalytic degradation of organic dyes is achieved.
Patent Information
- Application Number
- CN202411536522.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
Existing photocatalysts such as TiO2 and their composite materials are costly, complex in preparation process, and difficult to recover, and have problems of inefficiency when dealing with organic wastewater.
The preparation method of graphene nano-copper yttrium oxide composite powder is adopted, and anhydrous ethanol, starch, graphene, urea, copper sulfate solution and yttrium nitrate solution are added to ultrapure water, and the treatment is carried out through ultrasonic dispersion and supercritical reaction device. Graphene nano-copper-yttrium composite powder is obtained.
Graphene nano-copper yttrium composite powder significantly improves efficiency in photocatalytic degradation of organic dyes, low cost, relatively simple preparation and reusable, effectively solving the high cost and complex preparation problems of traditional photocatalysts.
Smart Images

Figure CN119406417A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photocatalytic wastewater treatment and new material technology, and specifically to a method for preparing graphene nano-copper yttrium oxide composite powder. Background Art
[0002] Photocatalysts, as a green and environmentally friendly treatment agent, have broad prospects in treating organic wastewater. Redox graphene, as a new type of two-dimensional material with a single layer of carbon atoms, has excellent adsorption properties for various dyes and metal ions, mainly due to the interaction between anions and cations. It has a very broad application prospect in treating dye wastewater, but the adsorbed graphene oxide will dissolve in water, which is not easy to recover and cannot be reused, resulting in great waste.
[0003] Patent CN115532248A discloses a method for preparing a graphene-titanium dioxide composite, which uses titanate and NaOH solution to react and then uses a hydrothermal method to load titanium dioxide on graphene, which has a higher photocatalytic efficiency than single titanium dioxide. Patent CN108047808A discloses a graphene additive for photocatalytic coatings and a preparation method thereof, which is made of graphene oxide, copper oxide powder, nano zinc oxide, nano titanium dioxide and solvent, has a three-dimensional porous structure, a large specific surface area, can increase the adsorption concentration, and achieve a higher photocatalytic performance. However, TiO2 and its composite materials, as more commonly used photocatalysts, have high costs, complex preparation processes and are not easy to recycle.
[0004] Copper oxide has a smaller interstitial energy than titanium dioxide, and has a certain treatment efficiency in photocatalytic degradation of dyes in some aqueous solutions, and its cost is lower. Therefore, copper oxide is a better choice in photocatalysis. Copper oxide nanorods have characteristics such as surface effect, quantum size effect, volume effect and macroscopic quantum tunneling effect. Compared with ordinary copper oxide, the nano size gives copper oxide nanorods special electrical, optical, catalytic and other properties. In terms of photocatalysis, nano copper oxide can better photocatalytically degrade organic dyes. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing graphene nano-copper yttrium oxide composite powder to solve the problems raised in the background technology.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing graphene nano-copper oxide composite powder comprises the following steps:
[0008] S1. Add anhydrous ethanol and starch to ultrapure water, stir evenly, add graphene, ultrasonically disperse for 40-60 minutes, add urea, copper sulfate solution and yttrium nitrate solution, stir evenly to prepare a mixed solution;
[0009] S2, adding the mixed solution into a supercritical reaction device, setting a heating program, keeping the temperature, cooling to room temperature, taking out the reactants, centrifuging, filtering, washing, and drying to obtain graphene nano-copper oxide composite powder;
[0010] The following raw materials are included in mass percentage:
[0011] Anhydrous ethanol 10-20%;
[0012] Starch 3.0-6.0%;
[0013] Graphene 1.0-4.0%;
[0014] Urea 10-20%;
[0015] Copper sulfate solution 12.0-16.0%;
[0016] Yttrium nitrate solution 2.0-5.0%;
[0017] Ultrapure water balance.
[0018] Furthermore, the starch is soluble starch.
[0019] Furthermore, the specific surface area of the graphene is 720-920m 2 / g.
[0020] It should be noted that the unique structure of graphene allows it to undergo π-π conjugation with compounds containing benzene rings, and it has a huge specific surface area, so graphene can be used to adsorb some organic pollutants in wastewater. Redox graphene (RGO) is a new type of two-dimensional material with a single layer of carbon atoms. Its surface is rich in a variety of active groups, mainly including a large number of oxygen-containing functional groups such as hydroxyl, carboxyl, and epoxy groups. The presence of these active oxygen-containing groups can provide necessary adsorption sites for pollutants, greatly improving the solubility of redox graphene and effectively avoiding agglomeration.
[0021] Furthermore, the mass fraction of the copper sulfate solution is 6%.
[0022] It should be noted that the photocatalysis of nano copper oxide is a technology that uses copper oxide as a catalyst to promote chemical reactions through light. In terms of environmental protection, copper oxide photocatalysis can be used to treat wastewater and waste gas. Organic matter and heavy metal ions in wastewater can be decomposed into harmless substances through copper oxide photocatalysis. Harmful gases in waste gas such as sulfur dioxide and nitrogen oxides can also be converted into harmless gases through copper oxide photocatalysis. In terms of energy development, copper oxide photocatalysis can be used in solar cells and photocatalytic water decomposition. Copper oxide nanorods have characteristics such as surface effect, quantum size effect, volume effect and macroscopic quantum tunneling effect. Compared with ordinary copper oxide, the nano size gives copper oxide nanorods special electrical, optical, catalytic and other properties. In terms of photocatalysis, nano copper oxide can better photocatalytically degrade organic dyes.
[0023] Furthermore, the mass fraction of the yttrium nitrate solution is 8%.
[0024] It should be noted that yttrium is a rare earth element that can be used as a central ion to complex with negatively charged anions as ligands. It can accommodate more ligands around it, and the coordination number is mostly 6, with a strong tendency to form complexes. On the one hand, rare earth ions form coordination bonds with organic ligands through electrostatic attraction, so they can be used as mordants in the field of textile engineering to improve the color fastness of natural dyes. On the other hand, the application of rare earth composite materials in adsorption materials also has great potential. Rare earth can coordinate with water in aqueous solution to form hydrated oxides. The hydrated oxides have low potential, high alkalinity, and a large number of positive charges on the surface, which attract anions dispersed in water. The hydroxyl groups contained in the rare earth hydrated oxides produce ion exchange reactions with anions to complete the adsorption treatment of organic waste dyes.
[0025] Furthermore, the pressure of the supercritical reaction device is 2-6 MPa.
[0026] Furthermore, the heating rate of the heating program is 10-16°C / min.
[0027] Furthermore, the heating temperature of the heating program is 120-140°C.
[0028] Furthermore, the insulation time of the insulation operation is 15-22 minutes.
[0029] Furthermore, the drying temperature is 120-160°C.
[0030] It should be noted that the graphene nano copper oxide yttrium composite powder in the present invention plays the role of a catalyst, a carrier and a flexible substrate at the same time. Nano copper oxide and nano yttrium oxide are uniformly intercalated and distributed in the pores and surface of the redox graphene, and the active oxygen-containing groups on the surface of the redox graphene provide a large number of adsorption sites to avoid agglomeration; at the same time, the copper oxide nanorods decorated with yttrium oxide have a high oxygen absorption or release capacity, and the synergistic interaction between yttrium oxide and copper oxide effectively inhibits the photocorrosion and leaching of metal oxides, and the effective charge distribution reduces the recombination rate of excitons, resulting in a significant improvement in the photocatalytic activity of the graphene nano copper oxide yttrium composite powder.
[0031] It needs to be reiterated that during the photocatalytic degradation of organic waste dyes, an electric field is formed at the interface between heterogeneous catalysts, resulting in the adsorption of pollutants on the catalyst surface. The first step is that the catalyst absorbs higher energy photons, generating electron-hole pairs on the photocatalyst. The valence band electrons (VB) absorb photons and move to the higher energy level conduction band (CB) by leaving positive holes on the valence band. These electron-hole pairs are used for the next redox reaction in the entire heterogeneous catalyst system. On the one hand, the holes in the VB are captured by water molecules in the mixture solution, thereby forming the second strongest oxidant, reactive hydroxyl radicals, responsible for the degradation of organic pollutants. On the other hand, the photoexcited electrons in the CB react with dissolved oxygen to form superoxides, which are again mixed with protons to produce hydroperoxyl radicals and then hydrogen peroxide. Subsequently, hydroxyl radicals are formed by the attack of photogenerated electrons on hydrogen peroxide, which are active species for the decomposition of pollutants, and all generated hydroxyl radicals oxidize organic pollutants into non-toxic small units. Yttrium oxide increases the active surface area of copper oxide and effectively generates excitons in the metal oxide system.
[0032] Compared with the prior art, the present invention has the following beneficial effects.
[0033] 1. Copper oxide nanorods have small gap energy, lower cost, and have characteristics such as surface effect, quantum size effect, volume effect and macroscopic quantum tunneling effect, which can better photocatalytically degrade organic dyes.
[0034] 2. Graphene has a huge specific surface area and is rich in a variety of active oxygen-containing groups, which can provide the necessary adsorption sites to avoid agglomeration.
[0035] 3. Yttrium is a rare earth element with a strong tendency to form complexes, and can effectively complete the adsorption treatment of organic waste dyes.
[0036] 4. The graphene nano copper oxide yttrium composite powder in the present invention plays the role of a catalyst, a carrier and a flexible substrate at the same time. Nano copper oxide and nano yttrium oxide are uniformly intercalated and distributed in the pores and surface of the redox graphene. The copper oxide nanorods decorated with yttrium oxide have a high oxygen absorption or release capacity. Yttrium oxide increases the active surface area of copper oxide and effectively generates excitons in the metal oxide system. The synergistic interaction between yttrium oxide and copper oxide effectively inhibits the photocorrosion and leaching of metal oxides. The effective charge distribution reduces the recombination rate of excitons. The photocatalytic activity of the graphene nano copper oxide yttrium composite powder is significantly improved, which has broad prospects in treating organic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 The graphene nano-copper yttrium oxide composite powder is prepared in Example 4 of the present invention.
[0038] Figure 2 The photocatalytic degradation efficiency of the composite photocatalyst powder prepared in Example 4 and the comparative example in degrading a methyl orange solution with a concentration of 10 mg / L under 30 W ultraviolet light illumination.
[0039] In the figure: CuO / rgo / Y2O3 is Example 1, and CuO / rgo is a comparative example.
[0040] Figure 3 The photocatalytic degradation efficiency of the composite photocatalyst powder prepared in Examples 1-4 and the comparative example in degrading a methyl orange solution with a concentration of 10 mg / L under 60W ultraviolet light illumination.
[0041] Figure 4 The photocatalytic degradation efficiency of the composite photocatalyst powder prepared in Example 4 and the comparative example under 150W ultraviolet light conditions for degrading a methyl orange solution with a concentration of 10 mg / L.
[0042] In the figure: CuO / rgo / Y2O3 is Example 1, and CuO / rgo is a comparative example. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] Example 1
[0045] S1. Weigh 62 g of ultrapure water into a beaker, add 10 g of anhydrous ethanol and 3 g of sweet potato starch, stir evenly, add 1 g of graphene, and after ultrasonic dispersion for 60 min, add 10 g of urea, 12 g of copper sulfate solution and 2 g of yttrium nitrate solution, stir evenly to obtain a mixed solution;
[0046] S2. Add the mixed solution into a supercritical reaction device, heat it to 120°C at a heating rate of 12°C / min, keep it warm for 15 minutes, the pressure is 5 MPa, cool it to room temperature, take out the reactants, centrifuge, filter, wash and dry them at a drying temperature of 120°C to obtain graphene nano-copper oxide yttrium composite powder.
[0047] The mass fraction of the copper sulfate solution is 6%; the mass fraction of the yttrium nitrate solution is 8%.
[0048] Embodiment 2:
[0049] S1. Weigh 52 g of ultrapure water into a beaker, add 14 g of anhydrous ethanol and 4 g of sweet potato starch, stir evenly, add 2 g of graphene, and after ultrasonic dispersion for 60 min, add 12 g of urea, 13 g of copper sulfate solution and 3 g of yttrium nitrate solution, stir evenly to obtain a mixed solution;
[0050] S2. Add the mixed solution into a supercritical reaction device, heat it to 130°C at a heating rate of 13°C / min, keep it warm for 15 minutes, the pressure is 5 MPa, cool it to room temperature, take out the reactants, centrifuge, filter, wash and dry them at a drying temperature of 140°C to obtain graphene nano-copper oxide yttrium composite powder.
[0051] The mass fraction of the copper sulfate solution is 6%; the mass fraction of the yttrium nitrate solution is 8%.
[0052] Embodiment 3:
[0053] S1. Weigh 40 g of ultrapure water into a beaker, add 16 g of anhydrous ethanol and 5 g of sweet potato starch, stir evenly, add 3 g of graphene, and after ultrasonic dispersion for 60 min, add 17 g of urea, 15 g of copper sulfate solution and 4 g of yttrium nitrate solution, stir evenly to obtain a mixed solution;
[0054] S2. Add the mixed solution into a supercritical reaction device, heat it to 135°C at a heating rate of 13.5°C / min, keep it warm for 15 minutes, the pressure is 5 MPa, cool it to room temperature, take out the reactants, centrifuge, filter, wash and dry them at a drying temperature of 150°C to obtain graphene nano-copper oxide yttrium composite powder.
[0055] The mass fraction of the copper sulfate solution is 6%; the mass fraction of the yttrium nitrate solution is 8%.
[0056] Embodiment 4:
[0057] S1. Weigh 29 g of ultrapure water into a beaker, add 20 g of anhydrous ethanol and 6 g of sweet potato starch, stir evenly, add 4 g of graphene, and after ultrasonic dispersion for 60 min, add 20 g of urea, 16 g of copper sulfate solution and 5 g of yttrium nitrate solution, stir evenly to obtain a mixed solution;
[0058] S2. Add the mixed solution into a supercritical reaction device, heat it to 140°C at a heating rate of 14°C / min, keep it warm for 15 minutes, the pressure is 5 MPa, cool it to room temperature, take out the reactants, centrifuge, filter, wash and dry them at a drying temperature of 160°C to obtain graphene nano-copper oxide yttrium composite powder.
[0059] The mass fraction of the copper sulfate solution is 6%; the mass fraction of the yttrium nitrate solution is 8%.
[0060] Comparative Example
[0061] S1. Weigh 29 g of ultrapure water into a beaker, add 20 g of anhydrous ethanol and 6 g of sweet potato starch, stir evenly, add 4 g of graphene, and after ultrasonic dispersion for 60 min, add 20 g of urea and 16 g of copper sulfate solution, stir evenly to obtain a mixed solution;
[0062] S2. Add the mixed solution into a supercritical reaction device, heat it to 140°C at a heating rate of 14°C / min, keep it warm for 15 minutes, the pressure is 5 MPa, cool it to room temperature, take out the reactants, centrifuge, filter, wash and dry them at a drying temperature of 160°C to obtain graphene nano-copper oxide composite powder.
[0063] The mass fraction of the copper sulfate solution is 6%.
[0064] The difference between this comparative example and Example 4 is that no yttrium nitrate solution is added.
[0065] 1. Test:
[0066] 0.1 g of the composite material adsorbent was added to 100 mL of ultrapure water and dispersed by ultrasonic machine for 10 min. Then 80 mL of 10 mg / L methyl orange dye was added, the pH of the solution was adjusted to 3.2-4.4, and homogenized. A certain amount of the mixed solution was taken and the concentration of methyl orange in the water was detected by ultraviolet spectrophotometer (detection wavelength is max = 505 nm), and the photocatalytic degradation efficiency of methyl orange dye within 100 min was tested.
[0067] 2. Test Results
[0068] Figure 3The photocatalytic degradation efficiency of the composite photocatalyst powder prepared in Examples 1-4 and the comparative example in degrading a methyl orange solution with a concentration of 10 mg / L under 60W ultraviolet light illumination.
[0069] 3. Results and Discussion
[0070] Depend on Figure 3 It can be obtained that the graphene nano-copper oxide yttrium composite powder prepared in Example 4 has the best photocatalytic degradation efficiency of degrading a methyl orange solution with a concentration of 10 mg / L under 60W ultraviolet light irradiation conditions, and a photocatalytic degradation efficiency of 68.9% is obtained within 100 minutes, and the equilibrium concentration is reached the fastest, and the degradation effect is the most stable; the graphene nano-copper oxide composite powder prepared in the comparative example has the worst photocatalytic degradation efficiency of degrading a methyl orange solution with a concentration of 10 mg / L under 60W ultraviolet light irradiation conditions, and a photocatalytic degradation efficiency of 10% is obtained within 100 minutes. This is because yttrium oxide with strong adsorption capacity is not added, only nano-copper oxide is intercalated and distributed in the pores and surface layers of the redox graphene, the ability of copper oxide nanorods without copper oxide decoration to absorb and decompose active oxygen is greatly reduced, and the photocorrosion and leaching of metal oxides are not inhibited, resulting in a significant decrease in the photocatalytic activity of the photocatalytic composite powder.
[0071] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0072] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing graphene nano-copper oxide composite powder, characterized in that: The preparation method comprises the following steps: S1. Add anhydrous ethanol and starch to ultrapure water, stir evenly, add graphene, ultrasonically disperse for 40-60 minutes, add urea, copper sulfate solution and yttrium nitrate solution, stir evenly to prepare a mixed solution; S2, adding the mixed solution into a supercritical reaction device, setting a heating program, keeping the temperature, cooling to room temperature, taking out the reactants, centrifuging, filtering, washing, and drying to obtain graphene nano-copper oxide composite powder; The following raw materials are included in mass percentage: Anhydrous ethanol 10-20%; Starch 3.0-6.0%; Graphene 1.0-4.0%; Urea 10-20%; Copper sulfate solution 12.0-16.0%; Yttrium nitrate solution 2.0-5.0%; Ultrapure water balance.
2. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The starch is soluble starch.
3. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The specific surface area of the graphene is 720-920m 2 / g.
4. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The mass fraction of the copper sulfate solution is 6%.
5. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The mass fraction of the yttrium nitrate solution is 8%.
6. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The supercritical reaction device has a pressure of 2-6 MPa.
7. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The heating rate of the heating program is 10-16°C / min.
8. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The heating temperature of the heating program is 120-140°C.
9. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The insulation time of the insulation operation is 15-22 minutes.
10. The method for preparing a graphene nano-copper oxide composite powder according to claim 1, characterized in that: The drying temperature is 120-160°C.
Citation Information
Patent Citations
Graphene additive used for photocatalysis coating, and preparation method thereof
CN108047808A
Preparation method of graphene titanium dioxide compound
CN115532248A